"A little while" more: Further Thoughts on Hartman's Nature as Paraclete1A redacted version of this essay appeared earlier this year in the special issue of PhilologicalQuarterly "About Geoffrey Hartman, " guest-edited by Frances Ferguson and Kevis Goodman. I am grateful to the editors for permission to expand it here. I would also like to thank Karl Dahlquist, Brian McGrath, and Joshua Wilner for their invaluable help in its drafting, and most especially Geoffrey himself, for his example as guide and teacher. Issue 2 (October 2015) - François, Anne-Lise
Abstract : This essay returns to the moment in  Wordsworth's Poetry, where Geoffrey Hartman designates Wordsworth's "nature" as the "paraclete" or comforter whom Jesus promises his disciples when he is gone. The essay reconsiders Hartman's reading of Wordsworth's nature as a self-canceling guide or agent of non-violent transition, and as a figure of substitution and displaced attachment, in the context of contemporary ecological crisis such as species extinction and habitat loss. Focusing on the phrase "a little while" that accompanies Jesus's promise of the paraclete in John and that would now seem to describe all that is left of the many species on this earth, I argue that Hartman's reading practice locates the paraclete not in the promised but deferred return of divine presence but in the already realized rhythm of small, necessarily circumscribed advances and withdrawals.